Road Cut Slope Stability Assessment under Region-Specific Rainfall Scenarios in Middle Hills of Nepal - Gyawali, Tunisha; Dahal, Bhim Kumar (Journal on Transportation System and Engineering, 2025)
Rainfall-induced landslides, especially in the non-engineered hill roads, have resulted in huge mortality and socio-economic losses in low-income countries like Nepal. In this study, road cut slope stability analysis has been done considering different soil slope scenarios from various road corridors, and incorporating the spatio-temporal distribution of rainfall for site-specific studies in Nepal. The average monsoonal rainfall distribution in the Middle Hills was obtained from satellite GPM IMERG data (2001-2020) to create rainfall regions. We then determined the region-specific rainfall for numerical analysis, and validated them against site slope stability conditions for recent year rainfall from nearby gauged station. Transient seepage analysis was done in Seep/W and Limit Equilibrium Method was employed for slope stability analysis in Slope/W of GeoStudio 2023 using Mohr-Coulomb parameters. Validation for the selected rainfall and soil parameters showed reasonable accuracy to site slope failure conditions and establishes the reliability of the methodology employed for road cut slope stability assessment for regional use. Future scope of this research would be the development of user-friendly versions, with charts and tables for safe cut slope design, and empowerment of field engineers with the knowledge and tools to promote best practices in resilient road construction across vulnerable hilly terrains of Nepal.